(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2017)
This article examines the relationship between Italy and the Arab states. As a result of its central geographic position, acting as a natural bridge between Europe and Africa, Italy is undoubtedly more exposed and vulnerable than other countries to any critical developments in the political and economic situation of this area, so it is understandable that it occupies an increasingly important position in Italian foreign policy. The aim has been to create a safety net around Italian maritime borders against the risks posed by an uncontrolled increase in migration (to which Italy is more exposed than other countries), the instability of North African energy resources and Islamist terrorists infiltrating Italian territory. Apart from examining the concerns regarding the Maghreb region that have become crucially important for Italian national interests (security, immigration, development, energy), the article analyses the salient elements of bilateral relations between Italy and the Maghreb countries, particularly Libya.